The Implementation of Basic Education Data System at Muhammadiyah 9 Elementary School, Palembang - Nurrohim, Muhammad Azmi; Febriyanti; Zulkipli; Kanda, Rabiel (MultiTech Publisher, 2024)
This research aims to examine the implementation of the DAPODIK program at Muhammadiyah 9 Elementary School in Palembang, including its supporting and inhibiting factors. It utilizes a qualitative descriptive approach with informants comprising the School Principal, Administrative Staff, and Operators. Data collection techniques include observation, interviews, and documentation, while data analysis involves data reduction, data presentation, and drawing conclusions. Data validity was ensured through technique and source triangulation. Findings indicate that the implementation of the DAPODIK program at SD Muhammadiyah 9 Palembang is fairly effective, focusing on directives, coordination, communication, and motivation. Factors supporting this include adequate facilities, competent human resources, and reliable internet connectivity. Conversely, challenges include data synchronization limitations and server downtime during DAPODIK updates. In conclusion, the DAPODIK program at SD Muhammadiyah 9 Palembang is generally effective, facilitated by effective guidance, motivation, and efficient coordination and communication.